Interprofessional Pharmacokinetics Simulation: Pharmacy and Nursing Students’ Perceptions - Cropp, Cheryl D. (Pharmacy (Basel), 2018)
Interprofessional practice between pharmacists and nurses can involve pharmacokinetic dosing of medications in a hospital setting. This study describes student perceptions of an interprofessional collaboration pharmacokinetics simulation on the Interprofessional Education Collaborative (IPEC) 2016 Core Competencies. The investigators developed a simulation activity for senior undergraduate nursing and second-year pharmacy students. Nursing and pharmacy students (n = 54, 91 respectively) participated in the simulation using medium-fidelity manikins. Each case represented a pharmacokinetic dosing consult (vancomycin, tobramycin, phenytoin, theophylline, or lidocaine). Nursing students completed head-to-toe assessment and pharmacy students gathered necessary information and calculated empiric and adjusted doses. Students communicated using SBAR (Situation, Background, Assessment, and Recommendation). Students participated in debrief sessions and completed an IRB-approved online survey. Themes from survey responses revealed meaningful perceptions in all IPEC competencies as well as themes of safety, advocacy, appreciation, and areas for improvement. Students reported learning effectively from the simulation experience. Few studies relate to this type of interprofessional education experience and this study begins to explore student perceptions of interprofessional education (IPE) in a health sciences clinical context through simulation. This real-world application of nursing and pharmacy interprofessional collaboration can positively affect patient-centered outcomes and safety.